2014
DOI: 10.5953/jmjh.2014.21.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Korean Geriatric Anxiety Inventory(K-GAI)

Abstract: Purpose:The purpose of this study was to test the validity and reliability of the Korean version of the Geriatric Anxiety Inventory (K-GAI). Methods: Two hundreds and thirty six elderly were participated to test K-GAI. Goldberg's short screening scale for anxiety was tested for criterion validity. Receiver operating characteristics (ROC) analysis was used for measuring sensitivity and specificity. Results: The obtained internal consistency was 0.88. There were significant associations between test and retest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Internal consistency is to check if responses are consistent between several questionnaires in order to verify the same concept, it is determined by ⍺ coefficient [30]. This study showed a Cronbach's ⍺ of .905 for all items.…”
Section: Discussionmentioning
confidence: 91%
“…Internal consistency is to check if responses are consistent between several questionnaires in order to verify the same concept, it is determined by ⍺ coefficient [30]. This study showed a Cronbach's ⍺ of .905 for all items.…”
Section: Discussionmentioning
confidence: 91%
“…Participants were assessed for depression and anxiety using the Korean version of the Geriatric Depression Scale (Bae and Cho, 2004 ) and the Korean version of the Geriatric Anxiety Inventory (Kim et al, 2014 ), respectively. Quality of Life was also evaluated with the World Health Organization Quality of Life (WHOQOL-BREF) Scale (Min et al, 2002 ).…”
Section: Methodsmentioning
confidence: 99%
“…A partial list of the questionnaire items in K-SGDS is listed in Table 1. Anxiety symptoms of the participants were evaluated using the Korean version of Geriatric Anxiety Inventory (K-GAI) [29]-a commonly used questionnaire to identify anxiety symptoms in older adults. GAI and K-GAI are used interchangeably in this paper.…”
Section: Geriatric Depression and Anxiety Assessmentmentioning
confidence: 99%
“…GAI and K-GAI are used interchangeably in this paper. The K-GAI consists of 20 questions with "yes" or "no" answers and a score of 7 or more is the cut off for suggesting anxiety [29]. A partial list of the questionnaire items in K-GAI is listed in Table 2.…”
Section: Geriatric Depression and Anxiety Assessmentmentioning
confidence: 99%